Systematic review and meta-analysis of head-to-head trials comparing sulfonylureas and low hypoglycaemic risk antidiabetic drugs - Vallo Volke; Urmeli Katus; Annika Johannson; Karolin Toompere; Keiu Heinla; Kertu Rünkorg; Anneli Uusküla (BMC Endocrine Disorders, 2022)
Abstract Background Safety of sulfonylurea drugs in the treatment of Type 2 Diabetes is still under debate. The aim of this study was to compare the all-cause mortality and cardiovascular adverse events of sulfonylureas and drugs with a low risk for hypoglycaemia in adults with type 2 diabetes. Methods Systematic review and meta-analysis of randomised controlled trials. Data sources: MEDLINE (PubMed, OVID), Embase, Cochrane Central Register of Controlled Trials, CINAHL, WOS and Lilacs. Study selection Randomised controlled head-to-head trials that compared sulfonylureas with active control with low hypoglycaemic potential in adults (≥ 18 years old) with type 2 diabetes published up to August 2015. The drug classes involved in the analysis were metformin, dipeptidyl peptidase-4 (DPP-4) inhibitors, sodium-glucose co-transporter-2 (SGLT-2) inhibitors and glucagon-like peptide-1 (GLP-1) receptor agonists. Outcomes The primary endpoint was all-cause mortality. The secondary endpoints were MACE, cardiovascular events and severe hypoglycaemia. Synthesis of results: Two reviewers checked study eligibility, independently extracted data and assessed quality with disagreements resolved through discussion. We assessed the risk of bias of the included studies using the Cochrane risk of bias tool for randomized trials v2. Pooled odds ratios (ORs) were estimated by using fixed effects model. The study is registered on PROSPERO (26/05/2016 CRD42016038780). Results Our final analysis comprised 31 studies (26,204 patients, 11,711 patients given sulfonylureas and 14,493 given comparator drugs). In comparison to drugs with low hypoglycaemic potential, sulfonylureas had higher odds for all-cause mortality (OR 1.32, 95% CI 1.00-1.75), MACE (OR 1.32, 95% CI 1.07–1.61), myocardial infarction (fatal and non-fatal) (OR 1.67, 95% CI 1.17–2.38) and hypoglycaemia (OR 5.24, 95% CI 4.20–6.55). Subsequent sensitivity analysis revealed differences in the effect of sulfonylureas, with an increased risk of all-cause mortality with glipizide but not the other molecules. Conclusion Our meta-analysis raises concern about the safety of SUs compared to alternative drugs involved in current analysis. Important differences may exist within the drug class, and glimepiride seems to have best safety profile.